The ballad of sexual dependency - Goldin, Nan 1953- (Aperture Foundation, 2012)
"A visual diary chronicling the struggle for intimacy and understanding between friends, family, and lovers -- collectively described by Goldin as her "tribe." Her work describes a world that is visceral, charged, and seething with life. First published in 1986, this reissue recognizes the persistent relevance and freshness of Nan Goldin's cutting-edge photography. Her lush color photography and candid style demand that the viewer go beyond the surface to encounter a profound intensity. As Goldin writes: "Real memory, which these pictures trigger, is an invocation of the color, smell, sound, and physical presence, the density and flavor of life." Through an accurate and detailed record of her life, Ballad reveals Goldin's personal odyssey as well as a more universal understanding of the different languages men and women speak, and the struggle between autonomy and dependency. Over the past twenty-five years, the influence of Ballad on photography and other aesthetic realms has continually grown, making the work a contemporary classic. Nan Goldin's story of urban life on the fringe was the swan song of an era that reached its peak in the early eighties. Yet it has captured an important element of humanity that is transcendent: a need to connect".--Book jacket
Reprint with new author's afterword. Previously published: New York, N.Y. : Aperture Foundation, 1986
Keywords: Goldin, Nan / 1953-; Goldin, Nan -- 1953-; Portrait photography; Photography, Erotic; Porträtphotographie; Erotische Photographie; Fotografie; Erotische Fotografie; Zweierbeziehung -- Motiv; New York, NY; Bildband